Factors Influencing Successful Negative Pressure Wound Therapy for Mesh Salvage After Hernia Repair - Kumar PJ, Girish; P, Ragumani; S, Manibalan (Journal of Neonatal Surgery, 2025)
Background: Incisional hernia repair with prosthetic mesh reduces recurrence but risks mesh infections, often requiring removal. Negative Pressure Wound Therapy (NPWT) enables mesh salvage, but success varies. This study identifies factors influencing NPWT success in mesh infections post-hernia repair. Methods: A retrospective cohort study at Chettinad Hospitals and Research Institute (January–December 2024) included 100 patients aged ≥18 years with mesh infections within 6 months post-hernia repair. Exclusions: hernia recurrence, mesh migration, laparoscopic repairs. Data on demographics, comorbidities, mesh type/position, infection profiles, and NPWT outcomes were analyzed using chi-square tests, t-tests, and multivariate logistic regression. Results: NPWT achieved a 76% salvage rate. Obesity (BMI ≥30 kg/m², p=0.03), diabetes (p=0.04), smoking (p=0.001), and ASA ≥3 (p=0.03) predicted failure. Polypropylene meshes (81.6% success, p<0.001) and onlay/sublay positions (p=0.02) had higher success than PTFE or intraperitoneal placements. Antibiotic resistance (p=0.02), purulent discharge (p=0.01), and wound dehiscence (p=0.002) increased failure. Conclusion: NPWT is effective for mesh salvage, with success driven by polypropylene mesh, extraperitoneal placement, and absence of smoking or resistance. Optimizing patient and surgical factors enhances outcomes